Biochar-Modified Layered Double Hydroxide for Highly Efficient on Phenol Adsorption - Amri Amri; Rezonsi Rezonsi; Nur Ahmad; Tarmizi Taher; Neza Rahayu Palapa; Risfidian Mohadi; Aldes Lesbani (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
All activities require drinking water. The existence of waste makes water unfit for consumption. Phenol waste is one example of waste that is often found. The toxic and corrosive nature of phenol is very dangerous for life, so its presence must be considered. The adsorption process was carried out using NiAl and ZnAl layered double hydroxides composites with biochar to eliminate the presence of phenol waste The adsorption process was carried out using NiAl and ZnAl layered double hydroxydes materials which were composited with biochar to eliminate the presence of phenol waste. NiAl-Biochar and ZnAl-Biochar composites were successfully prepared, as determined by XRD, FTIR, SEM, and BET analyses. NiAl layered double hydroxide surface area grew from 92.683 to 438.942 m2/g while ZnAl layered double hydroxide surface area increased from 9.621 to 58.461 m2/g. pHpzc of material is between 5.1 and 9.4. Optimal pH of NiAl and ZnAl layered double hydroxide is 3, optimum pH of NiAl-Biochar and ZnAl-Biochar is 5, and optimum pH of Biochar is 7. All kinetic and isotherm models for all materials were pseudo-second-order and Freundlich, respectively. NiAl-Biochar and ZnAl-Biochar have maximal adsorption capacities of 74.62 mg/g and 52.91 mg/g, respectively. The material's reusability indicates that NiAl-Biochar has superior qualities and may be reused for up to five cycles, followed by ZnAl-Biochar, NiAl layered double hydroxide, ZnAl layered double hydroxide, and Biochar. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).